Mitochondrial mass and mitochondrial membrane potential of peripheral lymphocytes: promising biomarkers of systemic lupus erythematosus - Zhao, Guanfei; Li, Haolong; Miao, Yutong; Cheng, Linlin; Chen, Yuying; Huang, Yuan; Zhao, Hongyun; Liu, Yongmei; Jing, Yipei; Wang, Shasha; Li, Yongzhe; Zhang, Rui (Frontiers in Molecular Biosciences, 2025)
BackgroundMitochondrial dysfunction is implicated in the pathogenesis of systemic lupus erythematosus (SLE). Single-cell mitochondrial mass (SCMM), low mitochondrial membrane potential (MMP-Low) in lymphocytes, and circulating mitochondrial DNA (mtDNA) can reflect mitochondrial impairment and may serve as potential novel biomarkers for SLE.PurposeWe investigated the diagnostic utility of MMP-Low and SCMM in lymphocytes, as well as circulating mtDNA levels, in patients with SLE and examined their correlation with disease activity.MethodsFlow cytometry was performed to detect MMP-Low and SCMM in peripheral lymphocytes from patients with SLE (n = 52) and healthy controls (HCs, n = 30). The level of circulating mtDNA was quantified using PCR.ResultsPatients with SLE exhibited significantly decreased MMP-Low in some peripheral lymphocyte subsets. Meanwhile, significantly increased SCMM in some lymphocyte subsets and circulating mtDNA were observed in patients with SLE. CD8+ T naïve (Tn) cell MMP-Low, CD8+ T effector memory cell MMP-Low, CD8+ T central memory (Tcm) cell MMP-Low, and SCMM-CD8+ Tn cells demonstrated a moderate diagnostic value for SLE, with an area under the curve (AUC) above 0.8. Both CD4+ Tcm MMP-Low and SCMM-CD3+CD4+ T cells were significantly associated with the SLE Disease Activity Index 2000 (SLEDAI-2K) and circulating mtDNA levels. These markers also showed significant alternations between inactive and active SLE.ConclusionOur data showed that patients with SLE exhibit mitochondrial dysfunction. Several MMP-Low and SCMM in CD8+T cell subsets could serve as potential biomarkers for diagnosing SLE. Additionally, CD4+ Tcm MMP-Low and SCMM-CD3+CD4+ T cells were associated with SLE disease activity.